Reviving the Commodity: Recycling Trash and Lacan’s Master Discourse - Merrill, Derek S. (Pivot: A Journal of Interdisciplinary Studies and Thought, 2015)
This paper examines popular practices of recycling that give insight into the subject’s position to capitalism, and questions to what degree recycling alters the capitalist mode of production. I argue that rather than expressing a desire to forgo participation in the market, as in one does not purchase new commodities and therefore avoids the ecologically destructive cycle of overconsumption and excessive accumulation of trash, recycling posits the subject as a connoisseur of trash. I examine some specific recycling practices to shift the conversation about recycling from a (pseudo) critique of capitalism’s excesses, to a deep psychic desire for completeness. To better understand the psychic structure coordinating the subject’s thoughts and actions to the market, I turn to Jacques Lacan’s Master discourse. Using the discourse of the Master clarifies recycling’s primary function to neo-liberal capitalism.